2017
DOI: 10.1186/s12917-017-1258-2
|View full text |Cite
|
Sign up to set email alerts
|

MRI characteristics for “phantom” scratching in canine syringomyelia

Abstract: BackgroundA classic sign of canine syringomyelia (SM) is scratching towards one shoulder. Using magnetic resonance imaging (MRI) we investigate the spinal cord lesion relating to this phenomenon which has characteristics similar to fictive scratch secondary to spinal cord transection.Medical records were searched for Cavalier King Charles spaniels with a clinical and MRI diagnosis of symptomatic SM associated with Chiari-like malformation (CM). The cohort was divided into SM with phantom scratching (19 dogs) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 40 publications
1
35
0
Order By: Relevance
“…Syringomyelia was first described in the cervical spinal cord and postulated to result from altered cerebrospinal fluid (CSF) flow dynamics at the craniocervical junction . Symptomatic dogs show signs of neuropathic pain and paresthesias, which often manifest as phantom scratch, focused on the head and neck region . However, in many dogs, SM also occurs in the thoracic and lumbar spinal cord and although thoracolumbar (TL) pain is frequently noted we also observed that many CKCS have lumbosacral (LS) pain .…”
Section: Introductionmentioning
confidence: 86%
“…Syringomyelia was first described in the cervical spinal cord and postulated to result from altered cerebrospinal fluid (CSF) flow dynamics at the craniocervical junction . Symptomatic dogs show signs of neuropathic pain and paresthesias, which often manifest as phantom scratch, focused on the head and neck region . However, in many dogs, SM also occurs in the thoracic and lumbar spinal cord and although thoracolumbar (TL) pain is frequently noted we also observed that many CKCS have lumbosacral (LS) pain .…”
Section: Introductionmentioning
confidence: 86%
“…MM is indebted to Professor Sir Patrick Bateson FRS (1938-2017 for alerting him to the issue of syringomyelia in Cavalier King Charles Spaniels, putting him in touch with CF and hence precipitating this study, and especially for his mentorship and friendship across the years. Data supporting this study are available at: https://figshare.com/articles/Cockburn_et_al_-_Syringomyelia_data/5357668…”
Section: Acknowledgementsmentioning
confidence: 99%
“…Reported clinical signs that may indicate pain include frequent scratching of the caudal head and neck area. However 'phantom scratching' towards one shoulder or neck region without skin contact is not necessarily associated with pain (Nalborczyk et al, 2017). Other signs include spinal hyperaesthesia (aversion to being touched especially in the cervical and thoracolumbar regions) and vocalisations resembling "screaming" after sudden head movements, when rising, and when the dogs is lifted under the sternum (Rusbridge and Knowler, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Asterisk in the above list represents clinical or behavioral signs of pain that are defined as vocalization (spontaneous, on picking up or after movement especially when recumbent and during the night), spinal pain, and changes in activity and behavior, which suggested avoidance or pain when jumping up or doing stairs, behavior change (aggression, withdrawn, anxious, described as more timid) and sleep disturbance …”
Section: Methodsmentioning
confidence: 99%